2009
DOI: 10.1161/strokeaha.108.543884
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous and Sinus Thrombosis in Women

Abstract: Background and Purpose-Little is known about the gender-specific manifestations of cerebral venous and sinus thrombosis, a disease that is much more common in women than men. Methods-We used data of the International Study on Cerebral Vein and Dural sinus Thrombosis (ISCVT), a multicenterprospective observational study, to analyze gender-specific differences in clinical presentation, etiology, and outcome of cerebral venous thrombosis. Results-Four hundred sixty-five of a total of 624 patients were women (75%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
284
2
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(312 citation statements)
references
References 26 publications
16
284
2
10
Order By: Relevance
“…Most studies reported female sex preference in patients affected with CSVT, with no gender difference in children and elderly based on gender specific risk factors. [4][5] Kalita et al, Koopman et al and stated that CVST was more frequently associated with oral contraceptive use, pregnancy, or puerperium. 6,7 In present study male gender (73.3%) was predominantly affected with CSVT than females.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reported female sex preference in patients affected with CSVT, with no gender difference in children and elderly based on gender specific risk factors. [4][5] Kalita et al, Koopman et al and stated that CVST was more frequently associated with oral contraceptive use, pregnancy, or puerperium. 6,7 In present study male gender (73.3%) was predominantly affected with CSVT than females.…”
Section: Discussionmentioning
confidence: 99%
“…Since female sex factors are one of the major predisposing factors triggering the underlying mechanism of thrombosis, female gender is one of the major risk factors with a frequency rate of 3 to 1, when compared with men 9 . Suggesting our cases that have no other identifiable risk factor for thrombosis other than female gender and puerperium, previous reports demonstrated a 65% of identifiable causes of CSVT in women are related to pregnancy, puerperium, oral contraceptive use, or hormonal therapies which are unique to women 5,9 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 17 clinical studies showed that oral contraceptive use, Leiden mutation of Factor V, and hyperHcy were recognized as statistically significant risk factors 8). A multinational (21 countries), multicenter (89 centers) prospective observational study entitled the International Study on Cerebral Vein and Dural Sinus Thrombosis (ISCVT) [9][10][11][12][13] examined 624 cases of CVT and reported that the prevalence of hyper-Hcy is 4.5%. However, Boncoraglio et al reported from Italy that 10 of 26 patients (38.5%) with CVT had hyper-Hcy7).…”
Section: Archivos De Medicina Issn 1698-9465 Journal Of Neurology Andmentioning
confidence: 99%